Thermal potentiation of chemotherapy by magnetic nanoparticles. (October 2013) - Torres-Lugo, Madeline; Rinaldi, Carlos
Clinical studies have demonstrated the effectiveness of hyperthermia as an adjuvant for chemotherapy and radiotherapy. However, significant clinical challenges have been encountered, such as a broader spectrum of toxicity, lack of patient tolerance, temperature control and significant invasiveness. Hyperthermia induced by magnetic nanoparticles in high-frequency oscillating magnetic fields, commonly termed magnetic fluid hyperthermia, is a promising form of heat delivery in which thermal energy is supplied at the nanoscale to the tumor. This review discusses the mechanisms of heat dissipation of iron oxide-based magnetic nanoparticles, current methods and challenges to deliver heat in the clinic, and the current work related to the use of magnetic nanoparticles for the thermal-chemopotentiation of therapeutic drugs.